Silica biogeochemistry across a grassland climosequence - Blecker, Steve W., author; Kelly, Eugene F., advisor; Ippolito, Jim, committee member; Chadwick, Oliver, committee member; Sutton, Sally, committee member (Colorado State University. Libraries, 2005)
The importance of primary mineral dissolution and formation of secondary minerals has been recognized as an important control on silica concentrations and fluxes in soil solutions and stream waters. Such reactions are important in understanding such earth surface processes as soil development, soil buffering against acid deposition and regulation of atmospheric carbon dioxide. Links between terrestrial and marine systems are also important in terms of Si, where Si-based diatoms play a large role in marine primary productivity. Assessments of the controls on silica export from the terrestrial environment tend to ignore the role of plant silica cycling and biogenic silica storage in soils and vegetation, assuming that mineral weathering reactions alone controls this flux. Most weathering studies have occurred in forested ecosystems; though weathering in grasslands is typically less intense, they cover up to 40% of the earth's land surface and may play an important role in global Si biogeochemistry. To this end, I employed a mass balance study of Si pools and fluxes along a grassland climosequence in the Central Great Plains. In general, shortgrass systems tend to have greater pools of soil biogenic Si than tallgrass systems though the plants in shortgrass systems add less Si to the soil annually. Though biologically mediated Si accounts for only a few percent of the total Si in these systems, I believe that this Si is far more labile than mineral Si. Although these grassland systems are less weathered than temperate and tropical forests, biological Si cycling appears to impact mineral weathering to a greater extent as compared to forested systems. To date, the biological fractionation of Ge during plant Si uptake has been deduced from studies of plants in situ, where isolation of source Si is difficult at best. I provide more solid evidence regarding the magnitude and direction of biologic Ge fractionation through a controlled greenhouse study, where source Ge/Si values are more easily isolated. Fractionation differences among grassland species were similar, with those species grown in a nutrient solution fractionating against Ge by roughly 82%, and those grown in different soil mediums fractionating against Ge by approximately 53%. However, the differences between these two groups (nutrient solution vs. soil grown vegetation) and differences between leaf and stem Ge/Si values point to potentially different uptake mechanisms in Ge compared to Si. Biologic Ge fractionation could be the result of differences in reactivity and speciation, as well as Ge toxicity and kinetically driven fractionation resulting from differences in molecular weight between Ge and Si. As Ge behaves as a pseudo isotope of Si, differences in Ge/Si ratios among major pools in terrestrial systems allows for the potential use of Ge/Si as a tracer of silicate weathering and Si flux in these systems, and can provide a valuable tool for studying weathering processes and Si cycling in terrestrial and marine systems. Trends of Ge sequestration in secondary minerals, and depletion in both biologic and aquatic pools were similar in direction to those of tropical systems but less in terms of magnitude. Overlap in Ge/Si ratios among the pools examined (plant, soil, stream) in the less intensely weathered grassland ecosystems confounds the utility of this particular isotopic tool in elucidating weathering relationships. This initial extensive look at grassland Si biogeochemistry provides promise in studying fluxes of terrestrial Si, though a combination of more intensive catchment scale studies and/or additional tools to Si mass balance and Ge/Si ratios will be necessary to clarify the complexities associated mineral weathering and the Si biogeochemistry in terrestrial systems.
Keywords: soil sciences; biogeochemistry